Asymmetric membranes prepared with trifluoromethylphenylated poly(ether ether ketone) for gas separation. (February 2015) - Yu, Yunwu; Liu, Siyuan; Wang, Yan; Zhang, Haibo; Li, Xiaobai; Jiang, Zhenhua; Liu, Baijun
A series of asymmetric membranes based on a trifluoromethylphenylated poly(ether ether ketone) (CF3 -PEEK) were prepared using a dry–wet phase inversion method. To obtain the asymmetric membranes with defect-free skin, the type and concentration of internal nonsolvent and the evaporation time were carefully investigated. The cross-section of membranes was characterized by scanning electron microscopy. The gas separation performance of asymmetric membranes was tested in terms of gas permeabilities and selectivities for helium, carbon dioxide (CO2 ), oxygen (O2 ), and nitrogen by the constant volume method. It was found that the permeabilities of asymmetric membranes were obviously higher than that of CF3 -PEEK dense membrane. The membranes in series 2 showed higher permeability for each gas while the separability for gas pair CO2 /O2 increased from 3.78 to about 6 comparing with that of the dense membrane.